2012
DOI: 10.1111/jac.12015
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Optimum Seeding Rate for Irrigated Maize in Texas is Concomitant to Growing Season Mean Daily Minimum Temperature

Abstract: Our study was conducted to determine agronomic optimum seeding rates (AOSR) for irrigated maize under a range of agroecological conditions in Texas. Environmental factors that affect irrigated maize production vary considerably across Texas. This variability imposes region-specific limitations on statewide maize seeding rate recommendations. Our research examined the efficiency of varying seeding rates on irrigated maize grain yields in five USEPA Level IV Ecoregions that comprise most of the irrigated maize-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, it is plausible that narrow row (<0.76 m) or twin row arrangement in maize production may promote greater temperatures in the middle canopy where the leaf subtending the ear and those immediately above and below the ear contribute a greater proportion of assimilates to developing grain tissues relative to other parts of the canopy (Eastin, 1969). Higher temperatures within this stratum of the canopy might promote accelerated leaf senescence (Badu‐Apraku et al, 1983) or increase leaf dark respiration (Kaše and Čatský, 1984; Thompson et al, 2013), thereby reducing photoassimilate availability for kernel development. In our study, differences in leaf senescence below the ear were visible between row arrangements (greater senescence in twin row arrangement) during reproductive stages, particularly during the 2011 growing season at Champaign, IL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible that narrow row (<0.76 m) or twin row arrangement in maize production may promote greater temperatures in the middle canopy where the leaf subtending the ear and those immediately above and below the ear contribute a greater proportion of assimilates to developing grain tissues relative to other parts of the canopy (Eastin, 1969). Higher temperatures within this stratum of the canopy might promote accelerated leaf senescence (Badu‐Apraku et al, 1983) or increase leaf dark respiration (Kaše and Čatský, 1984; Thompson et al, 2013), thereby reducing photoassimilate availability for kernel development. In our study, differences in leaf senescence below the ear were visible between row arrangements (greater senescence in twin row arrangement) during reproductive stages, particularly during the 2011 growing season at Champaign, IL.…”
Section: Discussionmentioning
confidence: 99%
“…At similar plant densities, lower yield in field corn at higher latitudes can be due to decreased amount of solar radiation and reduced crop growing season [6,7]. In southern climates, Thompson et al [8] found that higher nighttime temperatures were unfavorable for field corn yields and reduced crop yield in above-average plant densities.…”
Section: Introductionmentioning
confidence: 99%
“…Crop yields change from year to year due to local weather and management decisions such as new and improved crop cultivars, changes in tillage methods, improvements in artificial drainage techniques, improved fertilization, and other technological changes (Hofstrand, 2010). Intrarow spacing, competition for water, light, and nutrients, and growing season average daily minimum air temperature determine the optimum plant population for each environment (Hodges and Evans, 1990; Thompson et al, 2013). Ahmadi et al (1993) found quadratic relations between GY and plant population in two experiments and linear relations in another two experiments.…”
mentioning
confidence: 99%